PENERAPAN PRINSIP BUSINESS JUDGEMENT RULE TERHADAP DIREKSI ATAS PERBUATAN MELAWAN HUKUM KARYAWAN KARENA MENETAPKAN DISKON PEMBELIAN EMAS ANTAM SECARA SEPIHAK - Indriyani Kusumawati; Yeti Sumiyati (Faculty of Law, Maranatha Christian University, 2021)
Unlawful acts cannot be separated by a violation of one's rights. This research is based on the phenomenon of directors who are penalized for unlawful acts committed by their employees. In 2021, PT Antam appealed to the court because the board of directors felt aggrieved by the judge's decision to impose damages on the directors of PT Antam. In fact, those who do illegal acts to the detriment of consumers are Eksi Anggraeni and the two employees, Misdianto and Ahmad Purwanto through the lure of discounts without the approval of the company. Limited Liability Companies Law implicitly regulates the concept of legal protection that is already known in some countries, namely the principle of Business Judgement Rule. This principle can be used by directors as a basis for legal protection to achieve justice. Therefore, the purpose of this research is to review the responsibility of the board of directors for actions against employee law that stipulates discounts on the purchase of Antam gold unilaterally associated with the law of limited liability companies and review the application of the principles of Business Judgement Rule to directors who must be responsible for actions against the law of employees. The results of this study concluded that the directors of PT Antam cannot be held accountable. Furthermore, the application of the Business Judgement Rule principle has not been applied to this case, so legal protection to the board of directors is still ignored by the judge and has not shown justice.